Fungicide Sensitivity Shifting of Zymoseptoria tritici in the Finnish-Baltic Region and a Novel Insertion in the MFS1 Promoter - Mäe, Andres; Fillinger, Sabine; Sooväli, Pille; Heick, Thies Marten (Frontiers in Plant Science, 2020)
Septoria tritici blotch (STB) is caused by the ascomycete Zymoseptoria tritici and one of the predominating diseases in wheat (Triticum aestivum) in Europe. The control of STB is highly reliant on frequent fungicide applications. The primary objective of this study was to assess sensitivity levels of Z. tritici to different fungicide groups. The fungicides included in this study were epoxiconazole, prothioconazole-desthio, tebuconazole, and fluxapyroxad. A panel of 63 isolates from Estonia, Latvia, and Lithuania, and 10 isolates from Finland were tested. Fungicide sensitivity testing was carried out as a bioassay analyzing single pycnidium isolates on different fungicide concentrations. The average EC50 value in Baltic countries and Finland to epoxiconazole was high ranging from 1.04 to 2.19 ppm. For prothioconazole-desthio and tebuconazole, EC50 varied from 0.01 to 0.24 ppm, and 1.25 to 18.23 ppm, respectively. The average EC50 value for fluxapyroxad varied from 0.07 to 0.33 ppm. To explain the range of sensitivity, the samples were analyzed for CYP51 and Sdh mutations, as well as cytb G143A, CYP51 overexpression, and multidrug resistance (MDR). Frequencies of ZtCYP51 mutations D134G, V136A/C, A379G, I381V, and S524T in the Finnish-Baltic region were lower than in other European countries, but have increased compared to previous years. The frequency of cytb G143A conferring strobilurin resistance also augmented to 50–70% in the Z. tritici populations from Estonia, Finland, Latvia, and Lithuania. No Sdh mutations were found in this study, and neither strains of MDR phenotypes. However, we found a strain harboring a previously unknown transposon insertion in the promoter of the MFS1 gene, involved in drug efflux and multi-drug resistance. This new insert, however, does not confer an MDR phenotype to the strain.